Role of Social Media in Shaping Voting Patterns: A Comparative Study of 2018 and 2024 General Elections in Pakistan - Saleem, Maria; Hayat, Waseem; Akbar, Muhammad Jamsheed (Annals of Human and Social Sciences, 2024)
This paper explores the pivotal role of social media in shaping voting patterns by implementing Stimulus Organism Response psychological theory. In Pakistan factors such as caste, religion, ethnicity, feudalism, vote selling and it is further compounded by rural and urban divide, family loyalties, community affiliations and male headed family influence voting patterns. The emergence of social media facilitates the candidate to communicate with a number of people from different areas and demographics with just a single click. Social media campaigns are influencing people especially the new voters and to the women who cannot attend traditional campaigns programs. It is a quantitative study based on a questionnaire survey targeting a broader demographics and sample size was 167 participants. The questionnaire was validated through expert reviews and pilot testing. Findings showed that social media highly influenced the decision making of people during elections and people have trust on social media. Use of social media to literate people should be encouraged due to its accessibility and cost effectiveness.